Regulation of Financial Systems and Economic Growth - de Serres, Alain (OECD Economics Department Working Papers, 2006)
This paper examines whether regulation that is more conducive to competitive and efficient financial systems has a significant positive impact on sectoral output and productivity growth in a sample of 25 OECD countries. More specifically, following a methodology used by Rajan and Zingales (1998), the paper tests whether industries that depend more heavily on external sources of funding tend to grow faster in countries that have more competition-friendly regulation in markets for banking services and financial instruments. The regulatory indicators are assembled from surveys conducted by the World Bank on regulations in banking and securities markets. They point to substantial variations in the stance of regulation across countries, in particular with respect to the broad rules underpinning securities market transactions. The empirical analysis indicates that financial system regulation matters for output growth both in a statistical and economic sense